Haemodynamic Changes in Coronary Artery Bypass Grafting using Colloidal and Crystalloid Solutions - Mazur, A.; Gurin, P.; Babich, M. (Ukrainian Journal of Cardiovascular Surgery, 2019)
The study group included 40 patients who used hydroxyethylstarch (HES) 130/0.4 solution or 4% gelatine solution in the intraoperative infusion therapy program. The comparison group consisted of 40 patients, which were exclusively crystalloid solutions in the intraoperative period. The changes in the cardiac index (CI), blood pressure (BP), pressure in the pulmonary artery (PAP), central venous pressure (CVP), the results of complete and biochemical blood tests, electrolyte, acid-base and gas composition of the blood were analysed. The statistical analysis of the material was carried out by standard methods using the application package MS Excel 2007 and Stat Plus 2007 Professional. Estimated mean, standard errors, statistical significance, Student’s t-test were used to assess the intergroup difference, while the relationship between the indicators was determined by the Pearson correlation analysis. Changes in intracardiac haemodynamics occurring at the stages of off-pump coronary artery bypass grafting were studied. The obtained results showed that when using colloidal solutions, the values of central haemodynamics at the stage of distal anastomosis formation (CI, BP, PAP and CVP) were significantly higher than in patients treated with crystalloid solutions. However, the decline in central haemodynamics in patients treated with crystalloid solutions was not critical and allowed off-pump coronary artery bypass grafting to be performed in all patients without involvement of cardio-pulmonary bypass (CPB).